Fundamentals of Polymer-Clay Nanocomposites - Beall, G. W. (Gary W.); Powell, Clois E. (Clois Elbert), 1944- (Cambridge : Cambridge University Press, 2011)
'Written for graduate students, researchers, and practitioners, this book provides a complete introduction to the science, engineering, and commercial applications of polymer-clay nanocomposites. Starting with a discussion of general concepts, the authors define specific terms used in the field, providing newcomers with a strong foundation to the area. The physical and mechanical properties of polymer-clay nanocomposites are then described, with chapters on thermodynamics and kinetics, engineering properties, barrier properties, and flame retardancy. Mechanisms underpinning observed effects, such as UV resistance, solvent resistance, and hardness, are also explained. In-depth discussions of clay and clay surface treatment, fabrication, and characterization of nanocomposites are provided, and particular emphasis is placed on the proper use and interpretation of analytical techniques, helping readers to avoid artifacts in their own work. With commercial applications discussed throughout, and experimental results connected with theory, this is an ideal reference for those working in polymer science'--
Includes bibliographical references and index.
Keywords: Nanocomposites (Materials).; Polymer clay